Potato peeler machine - Sheikh Abu Talib, Sheikh Amir Safwan (2025)
An essential tool in commercial and industrial food processing, the potato peeler machine is made to remove the skin from potatoes quickly and evenly. Foodservice establishments and production facilities can save a significant amount of time and labor by using this automated device to streamline the labor-intensive task of hand peeling. The potato peeler that is available now is big and heavy. It is only suitable for big industries. The objective of this project is to make a potato peeler that is not so big and not heavy so it can be use at home for cooking purposes. Potato peelers efficiently remove the outer skin from potatoes while preserving the vegetable's texture and reducing waste by using abrasive surfaces or revolving blades. Potato peeling machines with advanced models can be customized to meet specific needs by adjusting the thickness of the peeling. Features like safety mechanisms to prevent accidents and adjustable peeling thickness are common in modern potato peeler machines. As a result, this project will help people who want to cook at home. They will have easier time cooking potatoes because this potato peeler machine can peel more than one potato at a time without consume any human energy. This way, people can cook faster and more efficient